Improving Confirmatory Testing for the Antimicrobial Resistance Surveillance Network in Ethiopia. (October 2020) - Wadhwa, Ashutosh; Parsons, Michele; Beyene, Degefu; Assefa, Dawit; Alebachew, Gebrie; Hazim, Carmen; Westercamp, Matthew; Kanter, Theresa; Thomas, Elizabeth; Dinku, Surafel Fentaw; Hailu, Kibra; Mohamed, Aynalem; et al.
Abstract : Background: In July 2017, the Ethiopian Public Health Institute (EPHI) launched an antimicrobial resistance (AMR) surveillance network at 4 sentinel laboratories. The National Clinical Bacteriology and Mycology Laboratory (NRL) at EPHI performs monthly confirmatory testing on a subset of isolates submitted by these sites. We assessed the existing confirmatory testing program to identify gaps and develop solutions, including a monitoring and evaluation (M&E) system. Methods: We assembled a technical working group (TWG) of key stakeholders. Laboratory site visits included workflow observation, process mapping, document review, and technologist interviews. Proposed solutions to observed gaps were drafted in formats consistent with their intended application. Feedback from the TWG was incorporated into final drafts. Available AMR network staff members were trained remotely, and they will train remaining staff. Results: Table 1 describes major gaps and solutions identified. Conclusions: Confirmatory testing provides a mechanism to evaluate laboratory testing proficiency, target improvements, and estimate surveillance data quality, yet standardized methods were lacking. Our efforts highlight key components of confirmatory testing programs and provide a model for use in laboratories with similar needs. Funding: None Disclosures: None